Blackout - Black, Peter Jay. (New York : Bloomsbury, 2015)
"The world's most destructive computer virus has been unleashed, and it's up to the Urban Outlaws--five tough kids dedicated to bringing justice to their city--to destroy it"--
"First published in Great Britain by Bloomsbury Publishing Plc in February 2015."
Keywords: Adventure and adventurers -- Fiction; Ability -- Fiction; Orphans -- Fiction; Computer viruses -- Fiction; Computers -- Fiction; Science fiction; Adventure stories; Ability -- Juvenile fiction; Orphans -- Juvenile fiction; Computer viruses -- Juvenile fiction; Computers -- Juvenile fiction; Science fiction; Fiction; Juvenile works; Science fiction